2019
DOI: 10.1186/s42506-019-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing in Shiraz University of Medical Sciences; a before and after study

Abstract: Background: Outsourcing is a kind of participation between public and private sector. This should be monitored and supervised to enhance the quality of outsourced services and to prevent new problems in this area. Shiraz University of Medical Sciences (SUMS) hospitals increasingly use outsourcing in recent years. Objectives: The present research aimed at comparing outsourced departments of SUMS from economic view, accessibility of services, and service quality during the years 2010-2012. Methods: A before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…18 Also, the satisfaction rate of personal clients and stakeholders can be further improved through outsourcing services. 19 Most studies are still cautious about outsourcing primary health care and public health. Scholars have noticed the effectiveness of health services outsourcing and a series of possible problems, which may affect the efficiency and service quality of outsourced institutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Also, the satisfaction rate of personal clients and stakeholders can be further improved through outsourcing services. 19 Most studies are still cautious about outsourcing primary health care and public health. Scholars have noticed the effectiveness of health services outsourcing and a series of possible problems, which may affect the efficiency and service quality of outsourced institutions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that outsourcing can increase patient satisfaction 18 . Also, the satisfaction rate of personal clients and stakeholders can be further improved through outsourcing services 19 …”
Section: Introductionmentioning
confidence: 99%
“…Showed that outsourcing has been successfully undertaken for provision of pharmaceutical services and service purchasing has been the used model (Khooban et al, 2013;Tourani et al, 2010). Outsourcing of clinical and non-clinical services as well as its positive and negative consequences has been studied in several more studies (Barati et al, 2019;Chen, 1999;Hsiao et al, 2009;Kahouei et al, 2016;Karimi et al, 2012;Siganporia et al, 2016). and in some cases, the outsourcing model has been mentioned too (Graham et al, 2019;Jannati et al, 2017;Zhiarfar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Khooban et al and Tourani et al showed that outsourcing had been successfully undertaken to provide pharmaceutical services, and service purchasing had been the used model (6,24). Outsourcing of clinical and non-clinical services, as well as its positive and negative consequences, has been studied in several more stud-ies (25)(26)(27)(28). Furthermore, in some cases, the outsourcing model has been mentioned (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%